Analisis Analisis Kesulitan Passing Bawah Bola Voli Pada Kelas Xi SMAN 13 Medan: Bola Voli - Purba, Ilham Ari Affandi Purba; Siregar, Samsuddin; Ritonga, M Fauzan; Putra, Rifqi Andriansyah (SABA JAYA PUBLISHER, 2024)
Underpassing is a crucial basic technique in volleyball, serving as the foundation forteam success. This research aims to analyze the difficulties of class XI students atSMAN 13 Medan in making down passes. The method used was a direct surveyduring volleyball practice. The results of the analysis show that the low selfconfidence factor has a significant effect on students' abilities. Of the 30 studentsanalyzed, the difficulty categories were divided as follows: